Guts and Brains An Integrative Approach to the Hominin Record - Roebroeks, Wil (LUP Academic, 2007)
The human brain and its one hundred billion neurons compose the most complex organ in the body and harness more than 20 per cent of all the energy we produce. Why do we have such large and energy-demanding brains, and how have we been able to afford such an expensive organ for thousands of years? Guts and Brains discusses the key variables at stake in such a question, including the relationship between brain size and diet, diet and social organization, and large brains and the human sexual division of labour. This interdisciplinary volume provides an entry for the reader into understanding the development of both early primates and our own species